2016
DOI: 10.1159/000443734
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Programming in Very Preterm Birth

Abstract: Very preterm (i.e., <32 weeks of gestation) infants admitted to the neonatal intensive care unit are compromised in their abilities to respond adequately to common threats like hemodynamic changes and reduced energy supplies, which is partly attributable to adrenocortical insufficiency. Conversely, later in life, these infants show features of increased glucocorticoid bioactivity, such as abdominal fat distribution, raised blood pressure, insulin resistance and diabetes mellitus type 2. It has been suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 98 publications
1
14
0
Order By: Relevance
“…Our findings are consistent with Meuwese and colleagues, who reported that young adults born very preterm showed elevated DHEAS and androstenedione, particularly when born small for gestational age (SGA) (11). We speculate that inconsistent data regarding the effect of preterm birth and birth weight on subsequent adrenal androgen secretion may be due to differences in gestational age, degree of illness, and/or growth between birth and 36 weeks PMA (24, 26, 35).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our findings are consistent with Meuwese and colleagues, who reported that young adults born very preterm showed elevated DHEAS and androstenedione, particularly when born small for gestational age (SGA) (11). We speculate that inconsistent data regarding the effect of preterm birth and birth weight on subsequent adrenal androgen secretion may be due to differences in gestational age, degree of illness, and/or growth between birth and 36 weeks PMA (24, 26, 35).…”
Section: Discussionmentioning
confidence: 95%
“…Based on previously published data from individuals born preterm or IUGR at term gestation, we had hypothesized that extremely preterm birth would result in increased cortisol and adrenal androgen concentrations at age 6 compared to term-born children (13, 6, 7, 11, 26, 34). Our results were both more complex and physiologically compelling.…”
Section: Discussionmentioning
confidence: 99%
“…Both these mechanisms can lead to a suppression of fetal hypothalamic CRH that may continue after birth. Indeed, studies showed that the pituitary response to exogenous CRH was impaired in preterm newborns [12], suggestive of enhanced central feedback suppression by glucocorticoids. Another mechanism contributing to RAI is the immaturity of adrenal cortex enzymes, notably decreased 11β-hydroxylase activity, which is necessary for the conversion of 11-deoxycortisol to cortisol [13,14].…”
Section: Relative Adrenal Insufficiencymentioning
confidence: 99%
“…Several studies have addressed the long-term impact of prematurity on HPA axis activity [12]. Evidence encompassed a higher corticosteroid production rate [30], and increases in the serum or salivary cortisol concentration during early morning, at nadir, or throughout the day in subjects born preterm were observed (Fig.…”
Section: Adrenocortical Function In Childhood and Its Clinical Correlmentioning
confidence: 99%
“…Given its effects on fat disposition and metabolism, the hypothalamus-pituitary-adrenal (HPA) axis has been implicated to play a role in the pathway leading to obesity [2,3]. Not only endogenous but also maternal glucocorticoids (GCs) appear to be involved.…”
Section: Introductionmentioning
confidence: 99%